Development of Interactive Multimedia for Early Readers with Dyslexia at an Inclusive Elementary School in Malang City - Eka Mariana Sari; Wahyudi Siswanto; Mohammad Efendi (Journal of ICSAR, 2021)
Interactive multimedia is an electronic system containing images, animation, and an interaction between the media and students. It considered that dyslexic student needs multisensory methods and media in the learning process as well. This study aims designing interactive multimedia development for early reading of dyslexic student and  finding out its effectiveness. The method used  is William W. Lee and Diana L. Owens’ (2004) development model. The procedures are: (1) Assessment / Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation.  The results of feasibility and effectiveness trials conducted by media experts  scored  96% means "very feasible". In addition, the assessment of the material experts also obtained 91.3% and the practitioner gave 87%, both of them were in the “very decent” category. The results of the assessment on subject’s early reading ability at baseline conditions (A1) ranging from 45% to 50%. Meanwhile, a significant increase was shown during the intervention condition (B), namely the subject’s ability of early reading increased from 65% to 75%. In addition, to determine the effectiveness of the interactive multimedia (intervention) in subject’s reading ability, it was  added the baseline conditions (A2) ranged from 80% to 90%. Based on the analysis, it showed that interactive multimedia of early reading for dyslexic is feasible and effective to be used in the learning process of early reading for dyslexic students.